Dampak Persepsi Kemudahan dan Kualitas Situs Web terhadap Keinginan Konsumen untuk Membeli di Tokopedia di Universitas Sangga Buana YPKP Bandung - Ekaputra, Adriansyah; Hersusetiyati, Hersusetiyati; Ruslin, Nadya (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2025)
This study aims to analyze the impact of perceived ease of use and website quality on consumers' purchase intention on the Tokopedia e-commerce platform at Universitas Sangga Buana YPKP Bandung. The findings indicate that both perceived ease of use and website quality have a positive and significant effect on consumers' purchase intention. Perceived ease of use has a regression coefficient of 0.640, while website quality has a regression coefficient of 0.249. The F-test shows that these two variables collectively have a significant impact on purchase intention, with an F-value of 256.029. The study concludes that to enhance consumers' purchase intention on Tokopedia, it is essential to continuously improve perceived ease of use and website quality, including user-friendly navigation, attractive design, optimal loading speed, and transaction security. Therefore, Tokopedia can be more effective in attracting and retaining consumers' purchase interest in the increasingly competitive e-commerce market.